47 Quantified mitral regurgitation and left atrial function in HFrEF: intraplay and outcome implications. (8th December 2021) - Malagoli, Alessandro; Rossi, Luca; Zanni, Alessia; Sticozzi, Concetta; Piepoli, Massimo Francesco; Benfari, Giovanni
Abstract: Aims: The debate about the independent prognostic responsibility of functional mitral regurgitation (FMR) is still in turmoil. Growing findings about the predictive role of left atrial (LA) function are emerging in several scenarios. This study aims to define FMR linkage to cardiovascular (CV) outcomes and the interplay with LA function in a prospective cohort of consecutive heart failure patients with reduced ejection fraction (HFrEF). Methods and results: 286 consecutive outpatients with chronic HFrEF were enrolled. FMR was quantified by effective regurgitant orifice area (EROA). Global peak atrial longitudinal strain (PALS) was measured by speckle tracking echocardiography (STE). The primary endpoint was defined as a composite of congestive HF hospitalization and CV death. The majority (81%) of patients were men (mean age: 67 ± 11 years, mean LVEF: 32 ± 6%). The median global PALS was 17.7% ranging from 2.7% to 49.2%. FMR was quantifiable in 240 (84%) patients. During a median follow-up period of 6.4 (IQR: 3.9–7.7) years, the primary endpoint occurred in 88 (31%) patients (35 HF admissions, and 53 deaths). EROA showed independent prediction for the primary endpoint [HR: 1.30 (1.05–1.57), P = 0.01]. The spline modelling of the risk by EROA values showed an excess event risk starting at about the EROA value of 0.1 cm 2 (Figure 1 ). There was a remarkable graded association between the EROA strata, even if tested per 0.1 cm 2 increase, and the risk of congestive HF hospitalization and CV death ( P = 0.0004). Any FMR grade presenting with reduced LA function (PALS < 14%) was associated with dismal outcome (event rate of 63 ± 10% for EROA exceeding 0.3 cm 2 and 49 ± 6% for EROA ≥0.1 cm 2 at 5 years). Conversely, the presence of EROA ≥0.1 in the context of preserved global PALS showed a better outcome (Figure 2 ). Conclusions: Our results refine the independent association between FMR and CV outcome among HFrEF outpatients. The risk of CV events starts at a low EROA value, reaching a severe level above the threshold of 0.3 cm 2 . Within a moderate EROA range, the LA function mitigates the clinical consequences of the mitral regurgitation, providing measurable proof of the interplay between the regurgitation and the LA compliance.